Central Africa Humid Tropics Transect Sentinel Landscape (CAFHUT): A stocktaking pilot study - Sonwa, D.J.; Numbisi, F.N.; Noumbissi, D.; Manga, F.E.; Levang, P.; Takoutsing, B.; Fosso, A.L.G.; Vidal, L.; Chiputwa, Brian; Foundjem-Tita, D.; Nghobuoche, F.; Piabuo, S.M.; et al. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
This publication is part of the Sentinel Landscape network initiative established in eight sites around the world representative of widely different biophysical and socioeconomic contexts. Here we present and summarize the results of the research and baseline studies carried out in the Central Africa Humid Tropics Transect sentinel landscape, four sites in Cameroon indicative of the African humid forest ecological zone.